Effect of the MySweetheart randomized controlled trial on birth, anthropometric and psychobehavioral outcomes in offspring of women with GDM - Gilbert, Leah; Quansah, Dan Yedu; Arhab, Amar; Schenk, Sybille; Gross, Justine; Lanzi, Stefano; Stuijfzand, Bobby; Lacroix, Alain; Horsch, Antje; Puder, Jardena J., MySweetheart Research group (Frontiers in Endocrinology, 2023)
Introduction: Gestational diabetes mellitus (GDM) may negatively affect offspring outcomes. A lifestyle intervention may therefore not only improve maternal, but also offspring outcomes. The effects of lifestyle interventions on birth, anthropometric, and psychobehavioral outcomes in offspring of women with GDM need further evidence. Design: The MySweetheart trial is a monocentric single-blind randomized controlled trial in 211 women with GDM. It tested the effect of a pre- and postpartum multidimensional interdisciplinary lifestyle and psychosocial intervention focusing on both the mothers and their infants and its effects on maternal (primary outcomes) and offspring (secondary outcomes) metabolic and psychobehavioral outcomes compared with guidelines-based usual-care. This paper focuses on offspring’s birth, anthropometric, and maternal report of psychobehavioral outcomes at singular timepoints. Methods: Women with GDM aged ≥18 years, between 24-32 weeks of gestation, speaking French or English were included and randomly allocated to either the intervention or to an active guidelines-based usual-care group using a 1:1 allocation ratio. The intervention lasted from pregnancy until 1 year postpartum and focused on improving diet, physical activity, and mental health in the mother. For the offspring it focused on supporting breastfeeding, delaying the timing of introduction of solid foods , reducing the consumption of sweetened beverages, increasing physical activity of the family, and improving parental responsiveness to infant distress, hunger, satiety and sleeping cues, and difficult behavior. Results: Adverse birth and neonatal outcomes rarely occurred overall. There were no differences between groups in offspring birth, neonatal, anthropometric, or psychobehavioral outcomes up to one year. After adjustments for maternal age and the offspring’s sex and age, there was a borderline significant between-group difference in birth length (β:-0.64, CI:-1.27; -0.01, p: 0.05), i.e., offspring of mothers in the intervention group were born 0.64 cm shorter compared to those in the usual-care group. Conclusion: This is the first pre- and postpartum multidimensional interdisciplinary lifestyle and psychosocial intervention in GDM focusing on both the mother and the offspring. It did not lead to a significant improvement in most birth, anthropometric, and psychobehavioral outcomes in offspring of women with GDM. ClinicalTrials.gov Identifier: NCT02890693